MODEL KAPABILITAS “CUSTOMER RELATIONSHIP MARKETING: PADA INDUSTRI TEPUNG TAPIOKA DI KABUPATEN PATI - Khoerul Umam (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
This study aims to identify and analyze the influence of market information and human capitalon the performance capabilities of CRM marketing company with variable inervening on tapiocastarch industry in Pati regency with a sample size of 66 people. The sampling technique used inthis research is purposive sampling. Analysis tools is the path analysis and the test results showthat the human capital market information and found to have a positive and significant impacton CRM capabilities. Market information shown to have positive and significant impact on theperformance of marketing, then the owner / entrepreneur will respond well to the changesthat occur in the company, so as to improve the performance of the company’s marketing.Human capital has a positive and significant impact on the performance marketing, means thatincreasing human capital, the company can exploit and develop the knowledge, competenciesand skills of its employees efficiently, so that will have an impact on increasing the company’smarketing performance. CRM capabilities have a significant positive effect on marketingperformance. CRM capabilities are not able to become an intervening variable between marketand human capital information with marketing performance. Thus the market information andhuman capital affects only the performance of the company’s marketing but not through CRMcapabilities.Keywords: Market Information, Human Capital, CRM Capabilities and Marketing Performance.